2011
DOI: 10.1177/016264341102600104
|View full text |Cite
|
Sign up to set email alerts
|

Using Speech Recognition Software to Increase Writing Fluency for Individuals with Physical Disabilities

Abstract: Students with physical disabilities often have difficulty with writing fluency, despite the use of various strategies, adaptations, and assistive technology (AT). One possible intervention is the use of speech recognition software, although there is little research on its impact on students with physical disabilities. This study used an alternating treatments design to compare the use of speech recognition software to word processing on first draft writing with students with physical disabilities. Areas examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…3/2018 provides a more accessible interface for people with disabilities preventing keyboard or mouse use. 25 When writing or typing, a user's tactile activity leads to the final output of content. With speech, however, the content is delivered using sound as a medium.…”
Section: Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…3/2018 provides a more accessible interface for people with disabilities preventing keyboard or mouse use. 25 When writing or typing, a user's tactile activity leads to the final output of content. With speech, however, the content is delivered using sound as a medium.…”
Section: Speechmentioning
confidence: 99%
“…When words are understood correctly, dictation software may help users with spelling and may reduce the need to correct mistyped words. 25,60 SR platforms can process a maximum number of WPM while maintaining accuracy (usually slightly greater than 100 WPM depending on the platform). User and software training, domain-specific dictionaries, and medical vocabularies can improve accuracy.…”
Section: Speechmentioning
confidence: 99%
“…Some studies investigated the effect of multimodal features on written convention. Three of the studies (Cullen et al, 2009;Garrett et al, 2011;Silió & Barbetta, 2010) utilized research questions that involved software or word processing features such as word prediction, spell checker, speech recognition, and text-to-speech. For example, Garrett et al examined "the effects of speech recognition software to word processing across written production rate and accuracy on first draft writing" (p. 27).…”
Section: Trends In Research Designmentioning
confidence: 99%
“…Three studies examined the effects of multimodality on lower order concerns and found positive impacts on the writing performance of students with disabilities. Two studies focused on the effects of technology scaffolds on lower order concerns by examining software tools (i.e., text to speech, word prediction, and talking word processor) used alone and/or in combination (Cullen et al, 2009;Silió & Barbetta, 2010), while the other explored the effect of speech recognition on fluency (Garrett et al, 2011). A common focus for these studies was the accuracy with which students produced words.…”
Section: Technology As a Tool For Writingmentioning
confidence: 99%
See 1 more Smart Citation